(untitled) (Eurasian Research Bulletin, 2023)
The article shows changes in coronary vessels in patients with thyrotoxicosis and the results of their observation. In recent years, the number of patients treated in the city of Bukhara and its hospitals has been increasing. 40 patients with CKD and its complications were selected for the cardiology department of the hospital, and in 30 of them, about 70% of the causes of the disease are mainly estimated by the activity of the thyroid gland. The causes of the underlying disease in this group of patients will be determined by taking samples of the thyroid gland. An increase in the hormone thyroxine or a condition associated with it leads to an acceleration of cardiac activity